Neutrophil extracellular traps in patients with pulmonary tuberculosis. - van der Meer, A; Zeerleder, S; Blok, D; Kager, L; Lede, I; Rahman, W; Afroz, R; Ghose, A; Visser, C; Zahed, A; Husain, M; Alam, K; et al. (BioMed Central, 2017)
Tuberculosis is a devastating infectious disease causing many deaths worldwide. Recent investigations have implicated neutrophil extracellular traps (NETs) in the host response to tuberculosis. The aim of the current study was to obtain evidence for NETs release in the circulation during human tuberculosis. For this we measured the plasma concentrations of nucleosomes in conjunction with neutrophil elastase, in 64 patients with active pulmonary tuberculosis and 32 healthy controls. Patients with active tuberculosis had elevated plasma levels of nucleosomes and elastase when compared with local healthy blood donors. Furthermore nucleosome and elastase levels showed a positive correlation. These findings provide the first evidence for the release of NETs in the circulation of patients with active pulmonary tuberculosis.